Molecular Approaches for Low-Cost Point-of-Care Pathogen Detection in Agriculture and Forestry - Baldi, Paolo; La Porta, Nicola (Frontiers in Plant Science, 2020)
Early detection of plant diseases is a crucial factor to prevent or limit the spread of a rising infection that could cause significant economic loss. Detection test on plant diseases in laboratory can be laborious, time consuming, expensive and normally requires specific technical expertise. Moreover in the developing Countries it is often difficult to find laboratories equipped for this kind of analysis. Therefore, in the last years a high effort has been made for the development of fast, specific, sensitive and cost-effective tests that can be successfully used in plant pathology directly in the field, by low-specialized personnel using minimal equipment. Nucleic acid-based methods have proven to be a good choice for the development of detection tools in several fields, such as human/animal health, food safety and water analysis and their application in plant pathogen detection is becoming more and more common. In the present review, the more recent nucleic acid-based protocols for point-of care plant pathogen detection and identification are described and analyzed. All these methods have a high potential for early detection of destructive diseases in agriculture and forestry; they should help making molecular detection for plant pathogens accessible to anyone, anywhere and at anytime. We do not suggest that on site methods should replace completely lab-testing, which remains crucial for more complex researches, such as identification and classification of new pathogens or the study of plant defence mechanisms. Instead, POC analysis can provide a useful, fast and efficient preliminary in field screening that is crucial in the struggle against plant pathogens.